Cloning and Characterization of P5CS1 and P5CS2 Genes from Saccharum officinarum L. under Drought Stress - Iskandar, Hayati Minarsih; Widyaningrum, Dwiyantari; Suhandono, Sony (Journal of Tropical Crop Science, 2014)
Increasing world sugar demand might be fulfilled with land extensification which include the use of dry area. Development of drought tolerance and high productivity sugarcane variety could be achieved  by plant genetic engineering. Under drought condition, proline will be accumulated and functioned as an osmoregulator in plant cells. ∆1-pyrroline-5-carboxylate synthase (P5CS) is one of the important enzymes in proline biosynthesis.  This enzyme is encoded by P5CS gene family. We cloned two homologous P5CS genes from sugarcane,  SoP5CS1 (Accession Number : KF178299) and SoP5CS2 (Accession Number : KF178300), which encode 729 and 716 amino acid polypeptides. The identity between these two genes was 74% based on nucleotide sequences. The SoP5CS1 gene had 98% identity with SbP5CS1 (Accession Number : GQ377719.1) and SoP5CS2 had 99% identity with SaP5CS (Accession Number : EF113257.1). In this experiment, sugarcane plantlets  were exposed to medium containing PEG 6000 (40%) for 12, 24, 48, and 72 hours. Proline concentration was measured after treatment and genes expression were analyzed by real time-qPCR. The results showed that the proline concentration was increased 12 folds (9.8 umol.g-1) after 48-hours stress treatment. The highest expression of SoP5CS1 occured at 24-hours treatment with approximately 16 times from plant without PEG (control plant) and decreased gradually at 48 and 72 hours treatment. The highest expression of SoP5CS2 occured at 24-hours drought stress with approximately 3.6 folds compared to control. In drought treatment, the expression level SoP5CS1 was higher than SoP5CS2 and has increased significantly at 12-hours treatment. It is suggested that the SoP5CS1 gene contributes more significantly to the production of proline during drought stress than SoP5CS2. Hence, SoP5CS1 could potentialy be used as a marker to screen sugarcane variety for drought tolerance and for the development of transgenic plant tolerant to drought.Keywords: cloning, drought, expression, P5CS, sugarcane